Challenges of Providing End-of-Life Care for Homeless Veterans. (May 2016) - Hutt, Evelyn; Whitfield, Emily; Min, Sung-Joon; Jones, Jacqueline; Weber, Mary; Albright, Karen; Levy, Cari; O'Toole, Thomas
Objective: To describe challenges of caring for homeless veterans at end of life (EOL) as perceived by Veterans Affairs Medical Center (VAMC) homeless and EOL care staff. Design: E-mail survey. Setting/participants: Homelessness and EOL programs at VAMCs. Measurements: Programs and their ratings of personal, structural, and clinical care challenges were described statistically. Homelessness and EOL program responses were compared in unadjusted analyses and using multivariable models. Results: Of 152 VAMCs, 50 (33%) completed the survey. The VAMCs treated an average of 6.5 homeless veterans at EOL annually. Lack of appropriate housing was the most critical challenge. The EOL programs expressed somewhat more concern about lack of appropriate care site and care coordination than did homelessness programs. Conclusions: Personal, clinical, and structural challenges face care providers for veterans who are homeless at EOL. Deeper understanding of these challenges will require qualitative study of homeless veterans and care providers.